Propensity score‐matched analysis of endoscopic resection for recurrent colorectal neoplasms: A pilot study. Issue 9 (5th May 2021) - Ohmori, Masayasu; Yamasaki, Yasushi; Iwagami, Hiroyoshi; Nakahira, Hiroko; Matsuura, Noriko; Shichijo, Satoki; Maekawa, Akira; Kanesaka, Takashi; Yamamoto, Sachiko; Higashino, Koji; Uedo, Noriya; Ishihara, Ryu; et al.
Abstract: Background and Aim: Local residual/recurrent colorectal lesions after endoscopic resection (ER) are difficult to treat with conventional ER. Underwater endoscopic mucosal resection (UEMR) and endoscopic submucosal dissection (ESD) are reportedly effective. We investigated the appropriate indications of ESD and UEMR for recurrent colorectal lesions. Methods: This single‐center, retrospective, observational study was conducted at a tertiary cancer institute. Patients who underwent UEMR or ESD for residual/recurrent colorectal lesions after ER from October 2013 to February 2019 were enrolled. Propensity score matching was performed between the UEMR and ESD groups to compare the clinical characteristics, treatment, and outcomes. Results: In total, 30 UEMRs and 21 ESDs were performed. Median (range) diameter of the lesions was 8 mm (2–22 mm) in UEMR and 15 mm (2–58 mm) in ESD. Median procedure time in UEMR was significantly shorter than that of ESD (4 min [2–15 min] vs 70 min [17–193 min], P  < 0.001). En bloc and complete resection rates of ESD were significantly higher than that of UEMR (73% vs 100%, 41% vs 81%, respectively). No adverse events occurred with UEMR, but there were two cases (10%) of delayed perforation with ESD. Neither group reported recurrence after treatment. Propensity score‐matched cases showed significantly shorter procedure time and hospitalization period in UEMR than in ESD. Conclusions: The outcomes of UEMR and ESD were comparable. UEMR could be a useful salvage therapy for small local residual/recurrent colorectal lesions after ER with shorter procedure time and hospitalization period.